Validitas Media Berbasis Android pada Materi Struktur dan Fungsi Asam Amino dan Protein - Topan Setiawan; Fitriana Ibrahim (Orbital: Jurnal Pendidikan Kimia, 2021)
The COVID-19 pandemic has forced major changes in the world of education. The application of social distancing to learning from home makes educators must be more creative in learning. The use of appropriate media in learning is very important to overcome these problems. One of the media used is android-based learning media. This research is continuation research of android application design in the subject of structure and function of amino acids and proteins. This research is limited to media validation. The instrument validation test stated that the instrument was valid with rcount greater than rtable at the number of N = 34 and a significance value of 5%. The reliability test of the validation instrument shows the rcount value of 0.880 and is greater than rtable 0.339 at the number of N = 34 and a significance value of 5%. The score of the questionnaire instrument was 3,196 obtained by averaging the scores from each category. It is in the range of 2.9-3.4 with a high category so that it can be interpreted that the application can be used as a learning media of the structure and function of the molecule.